2017
DOI: 10.1016/j.jval.2017.08.2634
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome among Healthcare Professionals working in Gondar University Hospital, Northwest Ethiopia: A Cross-Sectional Study

Abstract: BACKGROUND:Due to exhaustive working climate, health-care professionals (HCPs) are highly exposed to emotional strain and work-related stress that leads to burnout syndrome (BOS).AIM:We aimed to explore the prevalence of BOS among HCPs and delineate the factors that contribute to developing this emerging threat in HCPs working in Gondar University Hospital (GUH).METHODS:A cross-sectional study was conducted among HCPs using a self-administered validated questionnaire containing sociodemographic and job charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 31 publications
4
20
4
3
Order By: Relevance
“…All of the studies were cross-sectional studies [ 14 , 15 , 17 , 24 – 26 ] except one study which was cohort study design [ 16 ]. Of all the studies, three of them were conducted among nurses only [ 17 , 24 , 26 ], and the rest were conducted among healthcare professionals [ 14 16 , 25 ]. The total sample size for this review was 1654 nurses with a maximum sample of 369 from Amhara region [ 24 ] and a minimum sample of 75 from SNNPR [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the studies were cross-sectional studies [ 14 , 15 , 17 , 24 – 26 ] except one study which was cohort study design [ 16 ]. Of all the studies, three of them were conducted among nurses only [ 17 , 24 , 26 ], and the rest were conducted among healthcare professionals [ 14 16 , 25 ]. The total sample size for this review was 1654 nurses with a maximum sample of 369 from Amhara region [ 24 ] and a minimum sample of 75 from SNNPR [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence of burnout in this review was 39% (95% CI: 27% to 50%). Individually, the prevalence of burnout among nurses across the regions in Ethiopia ranges from 12% in Amhara [ 27 ] to 50.6% in Oromia [ 14 ]. The reason for those variations might be due to the difference in the study setting because two of the studies were conducted in hospitals and health centers, while five of the studies were conducted in hospitals only; this difference may result in variation in the prevalence of burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varios estudios han demostrado la asociación entre el síndrome de BO y los factores de riesgo como el sexo masculino, la edad más joven, el trabajo extrahospitalario, trabajos en turnos extras, (23)(24)(25)(26)(27)(28)(29)(30) con falta adecuada de sueño y mayor exigencia laboral entre otros factores de riesgo . Casi todos los estudios sobre el efecto del síndrome de BO concluyeron que los profesionales de la salud generalmente tenían un riesgo relativamente alto de agotamiento.…”
Section: Discussionunclassified
“…Bhagavathula et al 108 This was a cross-sectional study that aimed to identify pharmacy students' perception of research in India, Pakistan and Malaysia. The study surveyed 348 students and identified the majority had no research experience but were interested in pursuing a research project.…”
Section: Curricular Additions/ Considerationsmentioning
confidence: 99%